An A in Their Social Lives, but an F in School: Adolescent Perceptions of Texting in School. (September 2017) - Tulane, Sarah; Vaterlaus, J. Mitchell; Beckert, Troy E.
Text messaging, used by people of all ages, has become the preferred method of communication for teenagers. Teens spend a significant amount of their daytime hours in school. Schools have not readily accepted the use of cell phone technology for fear of academic dishonesty, distraction, and cyberbullying. The current study examined adolescent ( n = 218) attitudes concerning text messaging in school. The majority of adolescents (71%) supported text messaging in school. A phenomenological qualitative approach revealed that adolescents' experience with texting and school centers on student attention, connection (with family, friends, and emergency responders), and levels of regulation (personal, circumstantial, and school).